Roles of MAPK and spindle assembly checkpoint in spontaneous activation and MIII arrest of rat oocytes. - Wei Cui (Public Library of Science (PLoS), 2012)
Rat oocytes are well known to undergo spontaneous activation (SA) after leaving the oviduct, but the SA is abortive with oocytes being arrested in metaphase III (MIII) instead of forming pronuclei. This study was designed to investigate the mechanism causing SA and MIII arrest. Whereas few oocytes collected from SD rats at 13 h after hCG injection that showed 100% of mitogen-activated protein kinase (MAPK) activities activated spontaneously, all oocytes recovered 19 h post hCG with MAPK decreased to below 75% underwent SA during in vitro culture. During SA, MAPK first declined to below 45% and then increased again to 80%; the maturation-promoting factor (MPF) activity fluctuated similarly but always began to change ahead of the MAPK activity. In SA oocytes with 75% of MAPK activities, microtubules were disturbed with irregularly pulled chromosomes dispersed over the spindle and the spindle assembly checkpoint (SAC) was activated. When MAPK decreased to 45%, the spindle disintegrated and chromosomes surrounded by microtubules were scattered in the ooplasm. SA oocytes entered MIII and formed several spindle-like structures by 6 h of culture when the MAPK activity re-increased to above 80%. While SA oocytes showed one Ca(2+) rise, Sr(2+)-activated oocytes showed several. Together, the results suggested that SA stimuli triggered SA in rat oocytes by inducing a premature MAPK inactivation, which led to disturbance of spindle microtubules. The microtubule disturbance impaired pulling of chromosomes to the spindle poles, caused spindle disintegration and activated SAC. The increased SAC activity reactivated MPF and thus MAPK, leading to MIII arrest.